Independent Board of Commissioners, Gender Diversity, and Corporate Social Responsibility Disclosure: Evidence from Indonesia - Gebrella Nadia Fiorin Tantya Ivanna; Joni Joni (Goodwood Publishing, 2026)
Purpose: This study examines the impact of independent supervisory boards on CSR disclosure with board gender diversity as a moderating variable in Indonesia’s two-tier board system. Research Methodology: The sample in this study consists of 2,118 firm-year observations based on Indonesian-listed firms from 2017 to 2020. Multiple linear regression is used to estimate the models, and the generalized method of moments (GMM) method addresses endogeneity issues. Results: This study finds a positive correlation between independent supervisory boards and CSR disclosure, but board gender diversity does not significantly affect this relationship. Conclusions: Independent supervisory boards positively influence CSR disclosures in Indonesia’s two-tiered system. However, board gender diversity does not moderate this relationship, contributing new insights to CSR research in contrast to the one-tier systems in the US and Europe. Limitations: This study’s limitations include focusing on the quantity rather than the quality of CSR disclosures, manual data collection from firm reports, and reliance solely on a quantitative approach. Contributions: This study highlights the effectiveness of independent supervisory boards in CSR disclosure within Indonesia’s two-tier system and contrasts it with findings from one-tier systems in other countries.